Nitrogen Deposition Modulates Litter Decomposition and Enhances Water Retention in Subtropical Forests - Xing, Jinmei; Hu, Chun; Song, Chenggong; Wang, Keqin; Song, Yali (Forests, 2024)
Nitrogen (N) deposition influences litter decomposition and its water-holding capacity in forest ecosystems. Water conservation remains a priority, so understanding these interactions is vital for managing forests, especially in the Yunnan Plateau region. This study aimed to investigate the effects of simulated N deposition on litter decomposition and water-holding capacity in the Evergreen broad-leaf and Quercus aquifolioides forest in the central Yunnan Plateau. Indoor flooding experiments were performed alongside varied nitrogen deposition treatments. Litter decomposition rates under these treatments were evaluated using the Olson model. In the decomposition study, the N treatments in the Evergreen broad-leaved forest increased the remaining mass by 4.75%–17.50% and 2.09%–16.36% compared with the control (20.97 ± 0.44% and 42.43 ± 0.47%), while in the Quercus aquifolioides forest, the remaining mass of leaves and twigs decreased by 5.00% and 0.70% in the LN treatment compared with the control (35.47 ± 0.39% and 44.10 ± 1.18%) and the MN and HN treatments increased by 2.55%–8.13% and 5.61%–11.28%, respectively. Effects of increased N deposition on litter decomposition changed from promoting to inhibiting, as low N sped up decomposition but higher levels inhibited it. Additionally, N boosted the water-holding capacity of litter, especially in leaves. The litter from both forests displayed a notable ability to absorb water. Nitrogen deposition modulates litter decomposition and water retention properties. Specifically, high nitrogen deposition increases litter water-holding capacity by inhibiting the rate of litter decomposition, which in turn alters its mass remaining rate, lignin, and cellulose remaining rates. Efficient management of the studied forests leveraging nitrogen deposition can boost their water conservation potential, aiding in atmospheric precipitation absorption and surface runoff regulation.